2017
DOI: 10.1371/journal.pone.0189587
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic MRI to quantify musculoskeletal motion: A systematic review of concurrent validity and reliability, and perspectives for evaluation of musculoskeletal disorders

Abstract: PurposeTo report evidence for the concurrent validity and reliability of dynamic MRI techniques to evaluate in vivo joint and muscle mechanics, and to propose recommendations for their use in the assessment of normal and impaired musculoskeletal function.Materials and methodsThe search was conducted on articles published in Web of science, PubMed, Scopus, Academic search Premier, and Cochrane Library between 1990 and August 2017. Studies that reported the concurrent validity and/or reliability of dynamic MRI t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 86 publications
(163 reference statements)
0
25
0
1
Order By: Relevance
“…In their systematic review, Borotikar et al concluded that cine phase-contrast and real-time sequences were the two types of sequences that provided excellent validity and reliability for joint motion evaluation by MRI [17]. Cine phase-contrast sequences provide quantitative data, such as the three-dimensional (3D) pixel velocity in moving structures, coupled with anatomical images.…”
Section: Real-time Dynamic Mri Sequences and Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…In their systematic review, Borotikar et al concluded that cine phase-contrast and real-time sequences were the two types of sequences that provided excellent validity and reliability for joint motion evaluation by MRI [17]. Cine phase-contrast sequences provide quantitative data, such as the three-dimensional (3D) pixel velocity in moving structures, coupled with anatomical images.…”
Section: Real-time Dynamic Mri Sequences and Parametersmentioning
confidence: 99%
“…This is due to the existence of multiple and custom-built dynamic MRI sequences and the lack of standard/built-in dynamic musculoskeletal MRI sequences from the MRI scanners' original equipment manufacturers. Dynamic MRI is currently still not used in standard clinical practice for the management of musculoskeletal disorders [17]. Optimal dynamic MRI of the joint requires the following:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic kinematic MRI can allow for combined soft tissue evaluation with in vivo assessment of kinematics without the risks of ionizing radiation from fluoroscopy or CT . Different protocols have been described and validated, including cine‐phase contrast and, dynamic SPGR‐VIPR, and real‐time radial FLASH MRI .…”
Section: Kinematic Imagingmentioning
confidence: 99%
“…Dynamic kinematic MRI can allow for combined soft tissue evaluation with in vivo assessment of kinematics without the risks of ionizing radiation from fluoroscopy or CT. 66 Different protocols have been described and validated, including cine-phase contrast and, dynamic SPGR-VIPR, and real-time radial FLASH MRI. [67][68][69][70] The precision of measurements with dynamic MRI is similar to measurements from biplanar fluoroscopy, with precision 0.5-0.9 mm for translational measurements and 0.8-1.2 degrees for rotational measurements of the tibiofemoral and patellofemoral joints.…”
Section: Dynamic Imaging Techniquesmentioning
confidence: 99%